Comfort effects of weft-knitted structures on rowing shirts using IR thermography - Abreu, Maria José (2016)
A fundamental factor in high performance sportswear is the thermo-physiological wear comfort. The sportswear is responsible to support the thermal comfort of the wearer and consequently the thermoregulation, which means helping in body’s heat regulation by maintaining the skin temperature of 33°C and body’s core temperature of 37°C. Each sport has its own requisites and rowing is no exception. In the following investigation there were examined three different groups of water-repellent finished functional rowing shirts, featuring different knitting structures. The shirts were tested in a climatic chamber with a thermal manikin under constant conditions and afterwards analyzed using infrared thermography. The objective was to find out which sample shirts and knitting structures provide the best performance under different environmental conditions.